Defense Mechanisms of Xylopia aromatica (Lam.) Mart. in the Dry Season in the Brazilian Savanna - Campos, Felipe [UNESP]; Vieira, Maria [UNESP]; Sousa, Marília [UNESP]; Jorge, Letícia [UNESP]; Ferreira, Gisela [UNESP]; Marques, Marcia; Boaro, Carmen [UNESP] (MDPI, 2024)
Water availability and light during the dry and rainy seasons in the Cerrado may influence plants’ stomatal movement and the entry of CO2 for organic synthesis, which is the main electron drain. A lower stomatal conductance may contribute to the energy accumulated in the chloroplasts being directed towards the synthesis of compounds, which contributes to the activity of antioxidant enzymes to neutralize reactive oxygen species. Xylopia aromatica is a characteristic Cerrado species, and it is often recommended for recovering degraded areas. This study aimed to investigate the influence of the dry and rainy seasons on the metabolic adjustments of Xylopia aromatica in a portion of the Brazilian savanna in the state of São Paulo. In the rainy season, better photosynthetic performance led to greater investment in essential oil production. In the dry season, the plants may direct part of their reducing sugars to the syntheses of carotenoids and anthocyanins, which may help the antioxidant enzymes to neutralize reactive oxygen species. Carotenoids assist in the dissipation of photosystem energy, which has the potential to cause oxidative stress. During this season, lower stomatal conductance prevented excessive water loss. These results suggest the acclimatization of this species to the conditions of the Brazilian savanna.
Keywords: Annonaceae; antioxidant enzymes; bicyclogermacrene; photosynthesis; spathulenol; β-phellandrene